The Electronic Word of Mouth and Customer Retention at Retail Stores in Jaffna Market - Shivany, S.; Suganya, A.; Mary Theresha, S.; Queenmary Figurado, X.M.; Glodiya Fernando, N.I.; Lathursha, S.; Sinduja, K. (International Conference on Advanced Marketing: Marketing for Next Generation, University of Kelaniya, 2017)
Nowadays people mostly access social media therefore they get information regarding goods and service through e-WOM. E-WOM can be found in several different typologies known as one-to-one communication, one-to-many communication(websites) or many-to-many communication .Lack of Research Work on the topic of how Electronic Word of Mouth (E- WOM) has impact on customer retention made a gap for the research. Many researchers studied the influencing variable of customer retention in retail sector in other countries. Jaffna market, an developing retail platform needs the kind of research for strategic implication on technology application for E-WOM therefore, this research tries to make a link with E-WOM and customer retention. A framework was developed based on extensive review of Literature with two variables E-WOM and customer retention. a structured questionnaire was distributed among 100 customers who engaged with E-WOM in Jaffna retail market. The findings show that E-WOM has a significant positive impact on customer retention. There is a positive significant impact on customer retention on E-WOM. Findings clearly indicate that is imperative for retail sector to enhance customer retention. This due to growth of information Technology, instant popularity of websites such as face book, Twitter, Youtube and Wikipedia which have given liberty to customers in spreading there feedback quickly and conveniently.
Keywords: E-WOM; Customer; Retention; Retail stores in jaffna